IMPLEMENTATION OF AUGMENTED REALITY TECHNOLOGY IN NATURAL SCIENCES LEARNING OF ELEMENTARY SCHOOL TO OPTIMIZE THE STUDENTS LEARNING RESULT - Ali Fakhrudin; Yamtinah Sri; Riyadi Riyadi (IJIET (International Journal of Indonesian Education and Teaching), 2019)
In this research, the researcher developed new innovation in natural sciences learning of elementary school by implementing augmented reality technology. The method that used in this research was research and development method based on Borg and Gall theory which consists of ten stages: 1) research and information collecting, 2) planning, 3) develop preliminary form of product, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, 8) operational field testing, 9) final product revision, 10) dissemination and implementation. The result of this research is learning media of natural sciences learning in elementary school by utilizing augmented reality technology. Based on the implementation of experiment, it is obtained the data that learning process using augmented reality which is developed can optimize the students learning result.DOI: doi.org/10.24071/ijiet.2019.030101